2013
DOI: 10.1016/j.jns.2013.08.028
|View full text |Cite
|
Sign up to set email alerts
|

How long does it take to diagnose cervical dystonia?

Abstract: Background Dystonia is a neurological disorder characterized by involuntary twisting movements and postures. The neck is among the most commonly affected regions, and diagnosis can be made readily through a simple clinical evaluation. The goal of this study was to explore how long it took patients to receive a diagnosis of cervical dystonia after symptom onset. Methods A structured questionnaire was administered at outpatient clinics of a tertiary care academic medical center to 146 consecutively evaluated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
(13 reference statements)
1
22
0
1
Order By: Relevance
“…The results of our survey add to those from other single-center studies performed in Canada, Australia, and the USA [2][3][4]. These studies reported that diagnosis of AOD may be delayed for several years and that many patients visit numerous physicians in the interim.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of our survey add to those from other single-center studies performed in Canada, Australia, and the USA [2][3][4]. These studies reported that diagnosis of AOD may be delayed for several years and that many patients visit numerous physicians in the interim.…”
Section: Discussionsupporting
confidence: 74%
“…Three formal single-center studies showed that diagnosis of AOD may be delayed for several years; the average lag time between symptom onset and diagnosis was 3.8 years in an Australian study [2], 6.4 years in a Canadian survey [3], and 3.7 years in a study focusing on CD patients from the USA [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even for the most common and readily diagnosed subtypes of dystonia such as cervical dystonia, the mean time from onset of symptoms to diagnosis is 4–6 years. 3133 These delays in reaching a diagnosis often lead to frustration and mistrust of medical providers. Education and counseling are important for regaining trust so that patients are more likely to accept recommendations.…”
Section: Treatmentmentioning
confidence: 99%
“…Al lerdings ist die Prävalenz wegen methodischer Schwierigkeiten nicht exakt zu bestimmen. Die durchschnittliche Latenz zwischen Erstmanifestation und Diagnose einer isolierten Dystonie betrug 1995 knapp 4 Jahre und konnte in der Zwischenzeit nicht relevant verkürzt werden [28,34]. Dystonien sind ein heterogenes Krank heitsbild und stellen auch den erfahrenen Neurologen vor diag nostische Herausforderungen.…”
Section: Motivation Und Häufigkeitunclassified